Windows 10 plain & simple - Muir, Nancy 1954-; Miller, Michael 1958- (Microsoft Press, 2018)
Learn the simplest ways to get things done with Windows 10 Here's WHAT you'll learn • Navigate Windows 10 Fall Creators Update quickly, easily, and efficiently • Get online with the sleek Microsoft Edge web browser • Make the most of the Cortana personal assistant • Efficiently manage your email, calendar, photos, and more • Access your files from anywhere with Microsoft OneDrive • Help secure your computer and protect your data Here's HOW you'll learn • Jump in wherever you need answers • Follow easy steps and screenshots to see exactly what to do • Get handy tips for new techniques and shortcuts • Use Try This! exercises to apply what you learn right away.
Includes index. - Online resource; title from title page (Safari, viewed March 30, 2018)
Keywords: Microsoft Windows (Computer file); Operating systems (Computers); Systèmes d'exploitation (Ordinateurs); operating systems